Flame-retardant polypropylene containing expanded DOPO derivatives and preparation method thereof

By using expanded DOPO derivative flame retardant and other fillers in polypropylene materials, the problem of degradation of mechanical properties when polypropylene is improved is solved, efficient flame retardant performance and impact strength are improved, and halogen is avoided It is the toxicity of flame retardants and environmental pollution.

CN119220021BActive Publication Date: 2025-02-18SHOUGUANG WEIDONG CHENGUAN CHEM CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411756352.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-18
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

When existing polypropylene materials improve flame retardancy, they often lead to mechanical properties, especially the impact strength, and commonly used halogen flame retardants have toxicity and environmental pollution problems.

Method used

Using a flame retardant containing an expanded DOPO derivative, combined with linear low-density polyethylene, silane coupling agent modified glass fiber and nano calcium carbonate, the excellent flame retardant and improved flame retardant are prepared by melt coextrusion granulation process. Polypropylene material with impact strength.

Benefits of technology

At the lower amount of flame retardant added, the flame retardant performance and impact strength of polypropylene are significantly improved, the adverse effects of flame retardant on material properties are avoided, and the toxicity and environmental pollution of halogen-based flame retardants are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220021B_ABST
    Figure CN119220021B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of flame-retardant polypropylene, and specifically relates to a flame-retardant polypropylene containing an expanded DOPO derivative and a preparation method thereof, wherein the flame-retardant polypropylene comprises the following raw materials in parts by mass: 100 parts of polypropylene, 15-25 parts of an expanded DOPO flame retardant shown in Formula I, 3-10 parts of linear low-density polyethylene, 2-8 parts of silane coupling agent-modified glass fiber, and 1-8 parts of nano-calcium carbonate; the total mass of the silane coupling agent-modified glass fiber and the nano-calcium carbonate is 4-10 parts. The present invention prepares a novel expanded DOPO flame retardant by synthesis, which has a synergistic flame retardant effect of N and P, and can make polyolefin have a good flame retardant effect under a relatively low addition amount. At the same time, a certain amount of linear low-density polyethylene, silane coupling agent-modified glass fiber and nano-calcium carbonate are added to improve the mechanical properties of polypropylene, especially the impact performance is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame-retardant polypropylene, and in particular relates to a flame-retardant polypropylene containing an expanded DOPO derivative and a preparation method thereof. Background Art

[0002] Polypropylene is used in various scenarios due to its light density, good corrosion resistance, water resistance, and electrical insulation. However, polypropylene is a flammable material, and its UL-94 fire rating is for combustion, with an LOI of only 16.8%. In order to improve the flame retardancy of polypropylene, flame retardants are generally required. However, in order to achieve effective flame retardant properties for polypropylene, a large amount of flame retardants need to be added, which will have some adverse effects on the performance of polypropylene. At present, the common flame retardants for polypropylene in the prior art are halogen flame retardants. This type of flame retardant will release a large amount of toxic salt mist when burned, and has been banned in many occasions.

[0003] Intumescent flame retardant (IFR) is a composite flame retardant with the advantages of high safety, halogen-free, and low salt spray generation. It generally includes gas source, acid source and carbon source. When burned, it will form a carbonized layer of foam, which can play the role of heat insulation, oxygen isolation, and smoke suppression. It can also inhibit the generation of molten droplets and has a multi-element synergistic flame retardant effect. However, conventional intumescent flame retardants have the characteristics of migrating to the surface, poor weather resistance, and a tendency to reduce flame retardant performance after long-term use or storage.

[0004] The inventors have previously prepared a DOPO intumescent flame retardant containing P, N and S elements, achieving synergistic flame retardancy of P, N and S elements, and achieving excellent flame retardancy of polyolefin materials at a lower addition amount. However, the inventors found that even if the addition amount of the flame retardant has been reduced, the impact strength of polypropylene will still decrease. Therefore, there is still a need to further develop a flame retardant that can simultaneously improve the flame retardancy and mechanical properties of polypropylene. Summary of the invention

[0005] In order to solve the defects of the prior art that the flame retardancy and mechanical properties of polypropylene, especially the impact strength, are difficult to balance, the present invention proposes a polypropylene that can simultaneously improve the flame retardancy and mechanical properties. Specifically, the present invention adopts an expanded DOPO derivative flame retardant of the structure shown in Formula I, combined with a suitable filler, to achieve a polypropylene material with both excellent flame retardancy and impact strength. The present invention achieves the above-mentioned purpose through the following technical solutions:

[0006] A flame-retardant polypropylene containing an expanded DOPO derivative comprises the following raw materials in parts by weight: 100 parts of polypropylene, 15-25 parts of an expanded DOPO derivative shown in Formula I, 3-10 parts of linear low-density polyethylene, 2-8 parts of silane coupling agent modified glass fiber, and 1-8 parts of nano-calcium carbonate; the total weight of the silane coupling agent modified glass fiber and the nano-calcium carbonate is 4-10 parts;

[0007] Formula I.

[0008] Preferably, the flame-retardant polypropylene containing expanded DOPO derivatives comprises the following raw materials in parts by mass: 100 parts of polypropylene, 15-20 parts of expanded DOPO derivatives shown in formula I, 5-8 parts of linear low-density polyethylene, 3-5 parts of silane coupling agent modified glass fiber, and 2-5 parts of nano-calcium carbonate; the total mass parts of the silane coupling agent modified glass fiber and nano-calcium carbonate are 5-8 parts.

[0009] Preferably, the silane coupling agent modified glass fiber is obtained by first treating the glass fiber with hydrochloric acid, then immersing the glass fiber in an alcohol solution containing a silane coupling agent, and then drying the solution.

[0010] Specifically, the silane coupling agent modified glass fiber is obtained by a preparation method comprising the following steps:

[0011] (1) After the glass fiber is treated with hydrochloric acid, it is washed and dried to obtain the hydrochloric acid treated glass fiber;

[0012] (2) The glass fiber treated with hydrochloric acid is immersed in an alcohol solution containing a silane coupling agent, taken out after the immersion treatment, washed, and dried to obtain a silane coupling agent modified glass fiber.

[0013] Furthermore, in step (1), the glass fiber has a length of 5-20 mm and a diameter of 1-5 μm, a hydrochloric acid concentration of 0.5-1 mol / L, and a hydrochloric acid treatment time of 3-5 h; in step (2), the concentration of the silane coupling agent in the alcohol solution of the silane coupling agent is 1-5 wt %, the alcohol is selected from one of methanol, ethanol, and isopropanol, and the immersion time is 10-20 h; the silane coupling agent is selected from at least one of an aminosilane coupling agent, a cyanosilane coupling agent, and an epoxysilane coupling agent; and further, the aminosilane coupling agent is selected from γ-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, γ-diethylenetriaminepropylmethyldimethyl The cyanosilane coupling agent is selected from at least one of (2-cyanoethyl)triethoxysilane, 2-cyanoethyltrimethoxysilane and (2-cyanoethyl)triethoxysilane; the epoxysilane coupling agent is selected from at least one of 3-glycidyloxypropyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propyltriethoxysilane and 3-(2,3-epoxypropyloxy)propylmethyldimethoxysilane.

[0014] Furthermore, the silane coupling agent is a compound of aminosilane coupling agent and cyanosilane coupling agent in a mass ratio of 1-2:2-5. The inventors found that the glass fiber treated with the compounded silane coupling agent can improve the impact strength and high temperature and high humidity weather resistance of polypropylene.

[0015] Furthermore, there is no particular limitation on washing and drying, which are well known in the art. For example, after the hydrochloric acid treatment, the washing is performed with deionized water until the eluate is close to neutral (pH between 6.5 and 7); after the silane coupling agent treatment, the washing is performed with alcohol water having a volume concentration of 40-60% for 3-5 times; and the drying can be either oven drying or vacuum drying.

[0016] Preferably, the polypropylene melt index is 3-4 g / min; the linear low-density polyethylene (LLDPE) melt index is 0.6-0.8g / min. Linear low-density polyethylene has good toughness. The inventors mix a small amount of linear low-density polyethylene into the polypropylene material, which can effectively improve the toughness of the polypropylene composite material without adversely affecting other properties. However, it is necessary to strictly control the amount of linear low-density polyethylene added and its melt index. After a lot of experimental research, the inventors found that in the raw materials, based on 100 parts by mass of polypropylene, the amount of linear low-density polyethylene is 3-10 parts, preferably 5-8 parts. Too much LLDPE and too low melt index flow will lead to insufficient rigidity and weather resistance of the material; too little LLDPE or too high melt index cannot meet the toughening requirements.

[0017] Preferably, the particle size of nano calcium carbonate is 10-50 nm.

[0018] Furthermore, the DOPO intumescent flame retardant is prepared by a preparation method comprising the following steps: benzaldehyde and p-toluenesulfonyl hydrazide react to obtain an intermediate product TSH, and the intermediate product TSH reacts with DOPO to obtain the flame retardant. The specific reaction formula is as follows:

[0019] ;

[0020] Further, the reaction conditions of benzaldehyde and p-toluenesulfonyl hydrazide are 15-30°C in an alcohol solvent for 1-5 hours, and the molar ratio of benzaldehyde to p-toluenesulfonyl hydrazide is 1-2:1; the reaction conditions of the intermediate product TSH and DOPO are 50-70°C in an alcohol solvent for 40-60 hours, and the molar ratio of the intermediate product TSH to DOPO is 1-1.2:1. Further, the alcohol solvent is selected from at least one of methanol, ethanol, and isopropanol.

[0021] Furthermore, the raw material of the flame-retardant polypropylene containing expanded DOPO also includes auxiliary materials, such as 0.1-1 parts by mass of lubricant, 0.1-0.5 parts by mass of antioxidant, and 0.05-0.2 parts of ultraviolet absorber. The types of auxiliary materials are well known in the art, for example, the lubricant is selected from at least one of stearic acid, zinc stearate, magnesium stearate, polyethylene wax, and ethylene bisstearamide; the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, and antioxidant 168; the ultraviolet absorber is selected from at least one of UV 326, UV531, and UV944.

[0022] The present invention also provides a method for preparing the flame-retardant polypropylene containing the expanded DOPO derivative, comprising the following steps: uniformly mixing raw materials including the following components: polypropylene, the expanded DOPO derivative shown in formula I, linear low-density polyethylene, silane coupling agent modified glass fiber, and nano-calcium carbonate, melt co-extruding, and granulating to obtain a flame-retardant polypropylene masterbatch.

[0023] The process of melt extrusion granulation is well known in the art, for example, using a single screw extruder or a twin screw extruder.

[0024] Polypropylene is a widely used but flammable polymer, so flame retardants must be added to improve its flame retardant properties, but the amount of flame retardant added is relatively large, generally around 30wt% to reach the V0 flame retardant level of UL94. A large amount of flame retardant added will affect the mechanical properties of polyolefin materials on the one hand, and on the other hand, it will also increase the manufacturing cost of polyolefin materials. The present invention prepares a new type of intumescent DOPO flame retardant by synthesis, which has a synergistic flame retardant effect of N and P, and can make polyolefins have a good flame retardant effect under a lower addition amount. At the same time, a certain amount of linear low-density polyethylene, silane coupling agent modified glass fiber and nano calcium carbonate are added to improve the mechanical properties of polypropylene, especially the toughness, and the impact performance is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The product TS-0-DOPO 13 C NMR spectrum;

[0026] Figure 2 The product TS-0-DOPO 31 P NMR spectrum;

[0027] Figure 3 The product TS-0-DOPO 31 H NMR spectrum;

[0028] Figure 4 is the mass spectrum of the obtained product TS-0-DOPO;

[0029] Figure 5 These are photos of the samples of Example 1, Comparative Example 3, and Comparative Example 2 after being subjected to a vertical combustion test. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further explained below with specific implementation methods.

[0031] The melt flow index of the polypropylene used in the embodiment of the present invention is 3.5 g / min, the melt flow index of the linear low-density polyethylene is 0.8 g / min, and the D50 of the nano-calcium carbonate is 22.6 nm.

[0032] Preparation Example 1

[0033] Step (1)

[0034] ;

[0035] In a 100 ml round-bottom flask, (40 mmol) benzaldehyde and 40 ml ethanol were added respectively, followed by (40 mmol) TS. At room temperature, the stirring rate was controlled at 500 r / min and the reaction was carried out for 3 h. 200 ml pure water was added and stirred continuously. The filter cake was filtered and washed three times with 10% ethanol aqueous solution to obtain a sample powder, which was the product TS-H. Liquid chromatography showed that the purity was above 95%.

[0036] Step (2)

[0037] ;

[0038] In a 15 ml reaction tube, (4 mmol) TS-H dissolved in 4 ml ethanol was added, followed by (4 mmol) DOPO. The system was heated to 60°C and the stirring rate was controlled at 500 r / min. The reaction was continued for 48 h. After cooling to room temperature, the filter cake was obtained by filtration. The filter cake was washed three times with ethanol and water respectively, and then dried in an oven at 60°C to obtain the solid powder, i.e., the product TS-0-DOPO.

[0039] Figure 1 The product TS-O-DOPO obtained in Preparation Example 1 13 C NMR spectrum, the characteristic peaks are basically consistent with the TS-0-DOPO structure. Figure 2 The product TS-0-DOPO 31 P NMR spectrum confirms the presence of DOPO in the structure. Figure 3 The product TS-0-DOPO 31 H NMR spectrum. Figure 4 is the mass spectrum of the obtained product TS-0-DOPO. Figure 1-Figure 4 It was confirmed that the compound with the structural formula (I) was prepared in Preparation Example 1.

[0040] Preparation Example 2

[0041] (1) immersing glass fibers (length 5-10 mm, diameter about 4.2 μm) in 1 mol / L hydrochloric acid for 3 h, taking them out, washing them with water until the effluent is neutral, and drying them in an oven at 80° C. to obtain hydrochloric acid-treated glass fibers;

[0042] (2) The glass fiber treated with hydrochloric acid was immersed in an ethanol solution of a silane coupling agent with a mass concentration of 2 wt%, wherein the silane coupling agent was a mixture of γ-aminopropyltrimethoxysilane and 2-cyanoethyltrimethoxysilane in a mass ratio of 2:5, and after being immersed for 15 h, it was taken out, washed with a 40 vol% ethanol aqueous solution, and dried in an oven at 80°C to obtain a silane coupling agent modified glass fiber.

[0043] Preparation Example 3

[0044] The other conditions are the same as those in Preparation Example 2, except that in step (2), the mass concentration of the ethanol solution of the silane coupling agent is 5 wt %, and the silane coupling agent is a mixture of γ-aminopropyltrimethoxysilane and 2-cyanoethyltrimethoxysilane in a mass ratio of 1:2.

[0045] Preparation Example 4

[0046] The other conditions are the same as those in Preparation Example 2, except that in step (2), the silane coupling agent is γ-aminopropyltrimethoxysilane.

[0047] Preparation Example 5

[0048] The other conditions are the same as those in Preparation Example 2, except that in step (2), the silane coupling agent is 2-cyanoethyltrimethoxysilane.

[0049] Example 1

[0050] 100 parts by weight of raw materials of polypropylene, 15 parts by weight of TS-0-DOPO prepared in Preparation Example 1, 5 parts by weight of linear low-density polyethylene, 5 parts by weight of silane coupling agent modified glass fiber prepared in Preparation Example 2, 3 parts by weight of nano calcium carbonate, 0.5 parts by weight of zinc stearate, 0.2 parts by weight of antioxidant 1010, and 0.1 parts by weight of UV 326 latex were added to a high-speed mixer and mixed uniformly at a speed of 800 rpm to obtain a premix. The premix was added to a twin-screw extruder for melt extrusion, and then cut, granulated, and dried to obtain a flame-retardant polypropylene masterbatch.

[0051] Example 2

[0052] The other conditions were the same as those in Example 1, except that the amount of linear low-density polyethylene was 8 parts by mass.

[0053] Example 3

[0054] The other conditions were the same as those in Example 1, except that the amount of linear low-density polyethylene was 3 parts by mass.

[0055] Example 4

[0056] The other conditions were the same as those in Example 1, except that the amount of linear low-density polyethylene was 10 parts by mass.

[0057] Example 5

[0058] The other conditions are the same as those in Example 1, except that the silane coupling agent-modified glass fiber is prepared in Preparation Example 3.

[0059] Example 6

[0060] The other conditions are the same as those in Example 1, except that the silane coupling agent-modified glass fiber is prepared in Preparation Example 4.

[0061] Example 7

[0062] The other conditions are the same as those in Example 1, except that the silane coupling agent-modified glass fiber is prepared in Preparation Example 5.

[0063] Example 8

[0064] The other conditions were the same as those in Example 1, except that the amount of silane coupling agent modified glass fiber was 3 parts by mass, and the amount of nano calcium carbonate was 2 parts by mass.

[0065] Example 9

[0066] The other conditions were the same as those in Example 1, except that the amount of TS-0-DOPO prepared in Preparation Example 1 was 20 parts by weight.

[0067] Comparative Example 1

[0068] The other conditions were the same as those in Example 1, except that TS-0-DOPO prepared in Preparation Example 1 was not added.

[0069] Comparative Example 2

[0070] The other conditions are the same as those in Example 1, except that the TS-0-DOPO prepared in Preparation Example 1 is replaced by an equal mass of a DOPO derivative having the structure of the following formula (II) as a flame retardant:

[0071] Formula (II).

[0072] Comparative Example 3

[0073] The other conditions were the same as those in Comparative Example 2, except that the amount of the DOPO derivative having the structure of formula (II) was 25 parts by weight.

[0074] Comparative Example 4

[0075] Other conditions were the same as those in Example 1, except that no linear low-density polyethylene was added.

[0076] Comparative Example 5

[0077] The other conditions are the same as those in Example 1, except that the glass fiber is directly fed, that is, the glass fiber is not modified.

[0078] Application Examples

[0079] The TS-0-DOPO synthesized in the example was melt coextruded with polypropylene (melt flow index 3.5 g / min) to obtain a material. The flame retardant properties of the obtained flame retardant polypropylene material were tested according to different TS-0-DOPO addition amounts. The results are shown in Table 1 below.

[0080] The impact strength refers to GB / T 1843-2008, and the flexural modulus refers to GB / T 9341-2008. The impact strength retention rate is calculated by retesting the impact strength of the sample after 300 hours in a high temperature and high humidity environment of double 85 (85℃, 85RH%), and calculating the ratio of the impact strength before the high temperature and high humidity test.

[0081] Table 1 Flame retardant properties test of polypropylene materials

[0082] .

[0083] It can be seen from the data in Table 1 that the flame-retardant polypropylene provided by the present invention has excellent flame-retardant properties, and because a new type of expanded DOPO derivative flame retardant is used, the amount of flame retardant added is small and the impact on mechanical properties is small; at the same time, the reasonable combination of linear low-density polyethylene and modified glass fiber also solves the problems of impact strength and impact strength weather resistance of flame-retardant polypropylene.

[0084] Figure 5 The following are photos of the samples of Example 1, Comparative Example 3, and Comparative Example 2 after vertical combustion test. Three experiments were conducted in parallel for each sample. The three samples on the far left correspond to Example 1, the three samples in the middle correspond to Comparative Example 3, and the three samples on the right correspond to Comparative Example 2. It can be seen that the polypropylene material prepared by the present invention has a good flame retardant effect. The conventional DOPO flame retardant has a flame retardant effect that is not as good as the expanded DOPO derivative flame retardant shown in formula (I) of the present invention. The amount of flame retardant needs to be increased to achieve the desired flame retardant effect, which increases the cost on the one hand and reduces the mechanical properties, especially the impact strength on the other hand.

Claims

1. A flame retardant polypropylene comprising an expanded DOPO derivative, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polypropylene, 15-25 parts of an expanded DOPO derivative shown in formula I, 3-10 parts of linear low-density polyethylene, 2-8 parts of silane coupling agent-modified glass fiber, and 1-8 parts of nano-calcium carbonate; the total parts by weight of the silane coupling agent-modified glass fiber and the nano-calcium carbonate are 4-10 parts. Formula I.

2. The flame retardant polypropylene according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polypropylene, 15-20 parts of expanded DOPO derivatives shown in formula I, 5-8 parts of linear low-density polyethylene, 3-5 parts of silane coupling agent modified glass fiber, and 2-5 parts of nano-calcium carbonate; the total parts by weight of the silane coupling agent modified glass fiber and the nano-calcium carbonate are 5-8 parts.

3. The flame retardant polypropylene according to claim 1, characterized in that: The silane coupling agent modified glass fiber is obtained by first treating the glass fiber with hydrochloric acid, then immersing the glass fiber in an alcohol solution containing a silane coupling agent, and then drying the solution.

4. The flame retardant polypropylene according to claim 3, characterized in that: The silane coupling agent modified glass fiber is obtained by a preparation method comprising the following steps: (1) After the glass fiber is treated with hydrochloric acid, it is washed and dried to obtain the hydrochloric acid treated glass fiber; (2) The glass fiber treated with hydrochloric acid is immersed in an alcohol solution containing a silane coupling agent, taken out after the immersion treatment, washed, and dried to obtain a silane coupling agent modified glass fiber.

5. The flame retardant polypropylene according to claim 4, characterized in that: In step (1), the glass fiber has a length of 5-20 mm, a diameter of 1-5 μm, a hydrochloric acid concentration of 0.5-1 mol / L, and a hydrochloric acid treatment time of 3-5 h; in step (2), the concentration of the silane coupling agent in the alcohol solution of the silane coupling agent is 1-5 wt %, the alcohol is selected from one of methanol, ethanol, and isopropanol, and the immersion time is 10-20 h.

6. The flame retardant polypropylene according to claim 3, characterized in that: The silane coupling agent is selected from at least one of an aminosilane coupling agent, a cyanosilane coupling agent, and an epoxysilane coupling agent.

7. The flame retardant polypropylene according to any one of claims 3 to 6, characterized in that: The silane coupling agent is a compound of an aminosilane coupling agent and a cyanosilane coupling agent in a mass ratio of 1-2:2-5.

8. The flame retardant polypropylene according to claim 3, characterized in that: The polypropylene melt index is 3-4 g / min; the linear low-density polyethylene melt index is 0.6-0.8 g / min, and the nano calcium carbonate particle size is 10-50 nm.

9. The flame retardant polypropylene according to claim 1, characterized in that: The raw material of the flame-retardant polypropylene containing the expanded DOPO derivative further includes 0.1-1 parts by weight of a lubricant, 0.1-0.5 parts by weight of an antioxidant, and 0.05-0.2 parts by weight of an ultraviolet absorber.

10. The method for preparing the flame retardant polypropylene according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials are mixed evenly, melt-extruded, and granulated to obtain flame-retardant polypropylene masterbatch; the raw materials include: polypropylene, expanded DOPO derivatives shown in formula I, linear low-density polyethylene, silane coupling agent modified glass fiber and nano calcium carbonate.

Citation Information

Patent Citations

  • Flame Retardant For Epoxy Resin Containing Phosphonate And Phosphinate Functionality

    CN105906785A

  • Flame-retardant resin composition

    CN1518579A